Rapid Urbanisation in Zambia – the challenge of providing low-income housing in urban areas – 1964 to 2018: The case of the city of Lusaka - Chileshe, Alexander (Graduate School of Development Policy and Practice, 2020)
Soon after independence, in 1964, Zambia’s urbanisation proceeded very rapidly presenting significant housing problems to the independence government. In the last five decades, Zambia’s Capital City, Lusaka has been growing most rapidly. Unfortunately, most of this growth has been in informal settlements on insecure land because most residents cannot afford formal lowincome housing. Since 1964, government has undertaken several initiatives to bridge this low-income housing crisis. These include; providing complete housing, providing housing subsidies, providing serviced land, enacting new laws, establishing new institutions and even giving away housing for free. But all these initiatives, designed around the ruling political party governance system, have not yielded the desired results. As a result, the urban housing backlog which was estimated to be around 24,000 housing units at independence may now grow to over 3.0 million by 2030 if urgent action is not taken. Government has an opportunity to transform the urban housing sector by addressing weaknesses in the current laws and institutions, providing specific support to low-income households and encouraging private sector involvement. In all this, government must remember that context matters.